Improved Electrochemical Performance of Li1.25Ni0.2Co0.333Fe0.133Mn0.333O2 Cathode Material Synthesized by the Polyvinyl Alcohol Auxiliary Sol-Gel Process for Lithium-Ion Batteries - He Wang; Mingning Chang; Yonglei Zheng; Ningning Li; Siheng Chen; Yong Wan; Feng Yuan; Weiquan Shao; Sheng Xu (Advances in Condensed Matter Physics)
A lithium-rich manganese-based cathode material, Li1.25Ni0.2Co0.333Fe0.133Mn0.333O2, was prepared using a polyvinyl alcohol (PVA)-auxiliary sol-gel process using MnO2 as a template. The effect of the PVA content (0.0–15.0 wt%) on the electrochemical properties and morphology of Li1.25Ni0.2Co0.333Fe0.133Mn0.333O2 was investigated. Analysis of Li1.25Ni0.2Co0.333Fe0.133Mn0.333O2 X-ray diffraction patterns by RIETAN-FP program confirmed the layered α-NaFeO2 structure. The discharge capacity and coulombic efficiency of Li1.25Ni0.2Co0.333Fe0.133Mn0.333O2 in the first cycle were improved with increasing PVA content. In particular, the best material reached a first discharge capacity of 206.0 mAhg−1 and best rate capability (74.8 mAhg−1 at 5 C). Meanwhile, the highest capacity retention was 87.7% for 50 cycles. Finally, electrochemical impedance spectroscopy shows that as the PVA content increases, the charge-transfer resistance decreases.